Les cartes redistribuées de la gestion locale de l’eau : la mise en œuvre de la réforme « Gemapi » dans l’aire métropolitaine montpelliéraine - Sylvain Barone; Stéphane Ghiotti (Développement Durable et Territoires)
An important evolution has occurred in local water management since 2014 with the so-called Gemapi reform (management of aquatic environments and flood prevention) and its deployment at the local level. This reform upsets the balance between institutions and redistributes the cards between the various actors involved in this management, especially between the inter-municipalities and the watershed institutions. The objective of this paper is to better understand the modalities, the scope and the meaning of these reconfigurations, based on a case study of the Montpellier area. To do this, it proposes to analyze how the Gemapi reform was implemented, by placing this process in a specific local context and management trajectory. Two main lessons emerge: a lack of clarification of roles; a trend towards the affirmation of inter-municipalities and the weakening of watershed institutions, some of the implications of which we will mention.